Resiliensi Multidimensi Kepala Sekolah Dasar Negeri di Indonesia: Sebuah Studi Fenomenologi tentang Perjalanan dari Bertahan Menuju Berkembang - Aris Suharyadi (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
This study aims to explore the phenomenological experience of elementary school principals in transitioning their leadership from the surviving to thriving phase, as well as identifying the factors that form this multidimensional resilience. The research uses a qualitative approach with phenomenological methods. The research was carried out at SD Negeri Banguntapan, Bantul Regency, in September 2025–March 2026 with the subjects of the principal and teachers. Data was collected through in-depth interviews using interview guidelines. Data analysis is carried out through data condensation, data presentation, and a conclusion drawn, while data validity is checked through source triangulation and member check. The results showed that the principal's experience of resilience in moving from the defensive phase to developing was reflected in a calm attitude, positive thinking, focus on solutions, identifying the causes of problems, building open communication, and maintaining relationships with school residents and stakeholders. Factors that form resilience include five dimensions. The physical dimension appears in efforts to maintain health, stamina, and work energy; emotional dimension in emotional control and positive attitudes; psychological dimensions of motivation, responsibility, confidence, commitment, and ability to rise; social dimension in support of family, teachers, committees, parents, and the environment; as well as the spiritual dimension of the consistency of worship and religious values as a source of strength. The findings confirm that the resilience of school principals is a multidimensional process to transform from surviving to developing that is built dynamically through the interaction of personal and environmental resources.